Síntese e caracterização de materiais nanoporosos para pirólise catalítica de óleos pesados - Costa, Maria José Fonseca (2008)
The present work reports the study of nanoporous structures, aiming at their use in research directed to the current demand of the petroleum industry to value heavy oil. Initially, two ways were chosen for the synthesis of porous structures from the molecular sieves of type Si-MCM-41. In the first way, the structure MCM-41 is precursory for heteroatom substitutes of silicon, generating catalyst of the type Al-MCM-41 from two different methods of incorporation of the metal. This variation of the incorporation method of Aluminum in the structure of Si-MCM-41 was carried out through the conventional procedure, where the aluminum source was incorporated to the gel of synthesis, and the procedure post-synthesis, where the Aluminum source was incorporated in catalyst after the synthesis of Si-MCM-41. In the second way, the MCM-41 acts as a support for growth of nanocrystals of zeolite embedded in their mesoporous, resulting in hybrid MCM-41/ZSM-5 catalyst. A comparative analysis was carried through characterizations by XRD, FTIR, measures of acidity through n-butylamine adsorption for TGA, SEM-XRF and N2 adsorption. Also crystalline aluminosilicate with zeolitic structure MFI of type ZSM-5 was synthesized without using organic templates. Methodologies to the preparation of these materials are related by literature using conventionally reactants that supply oxides of necessary silicon and aluminum, as well as a template agent, and in some cases co-template. The search for new routes of preparation for the ZSM-5 aimed at, above all, the optimization of the same as for the time and the temperature of synthesis, and mainly the elimination of the use of organic templates, that are material of high cost and generally very toxic. The current study is based on the use of the H2O and Na+ cations playing the role of structural template and charge compensation in the structure. Characterizations by XRD, FTIR, SEM-XRF and N2 adsorption were also conducted for this material in order to compare the samples of ZSM-5 synthesized in the absence of template and those used industrially and synthesized using structuring